Implementasi Program EDELWIS: Membangun Kesadaran Kesehatan Melalui Sosialisasi dan Pengecekan Gula Darah - Hamda, Nuhan Izza; Walla, Muhammad Arief Sebastian; Putra, Adityo Arya; Putra, Muhammad Rifqy Ramadhani; Fandra, Fadhilla Izzatul; Septi, Cici Liara; Firlyanda, Bilqiis Aanisah; Widodo, Aris Slamet; Mustafa, Mustafa (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
EDELWIS program (Early Detection and Healthy Lifestyle) program is an activity initiative carried out by Real Work Lecture (KKN) students at Sekolah Indonesia Mekkah (SIM) with the aim of raising awareness about diabetes and the importance of early detection of diabetes through blood sugar checking and a healthy lifestyle among students. Diabetes mellitus, especially type 2, is increasingly found at a young age due to unhealthy diet and lack of physical activity. Based on the need assessment, it was found that most students in SIM have limited knowledge about diabetes and its prevention. Therefore, the EDELWIS program was designed to provide direct education on the risks of diabetes, the importance of early detection, and how to maintain health through healthy eating and regular exercise. The implementation method of this program includes initial socialization, monitoring sugar consumption using paper templates, and checking students' blood sugar levels. The socialization was conducted in classes VII to XII with an interactive approach through lectures, questions and answers, and group discussions. The results of the program showed significant improvements in students' knowledge, attitudes, and behaviors related to healthy lifestyles. Students who participated in this program began to reduce the consumption of sweet foods and pay more attention to their nutritional intake. The high participation of students in each stage of the activity shows the effectiveness of the approach used. However, there were some challenges, such as students' difficulty in consistently recording sugar intake and anxiety related to blood sugar check results. Therefore, further education is needed on the practical steps to be taken if the test results indicate a risk of diabetes. Overall, the EDELWIS program has successfully increased health awareness among SIM students and has the potential to be implemented in other schools both in Indonesia and abroad. This program is also one of the implementations of the Tri Dharma of Higher Education in the field of community service, providing direct benefits for students and valuable experience for students.